Bangladesh’s groundwater trade-offs from decarbonizing irrigation through solar-powered pumps - Alam, Mohammad Faiz; Mitra, Archisman; Mahapatra, Smaranika; Pavelic, Paul; Buisson, Marie-Charlotte; Habib, A.; Saha, T. K.; Haque, A.; Sikka, Alok (Springer, 2025)
Solar-powered irrigation systems are being scaled globally, especially in South Asia, to mitigate agriculture’s carbon emissions while addressing water–energy–food nexus challenges. However, this expansion raises concerns that solar irrigation could exacerbate groundwater overexploitation. Here we assess groundwater trade-offs of solar irrigation deployment in Bangladesh by comparing farmers’ water use for dry season paddy cultivation under diesel pumps and a solarized fee-for-service model. After accounting for soil, variety, land type and sowing time, no significant difference in terms of water application was found between solar (694–1,014 mm) and diesel (663–775 mm) plots in 2021–22 and 2022–23. A marginal 4.2 percentage point increase in dry season paddy area was observed under solar irrigation. Groundwater modelling shows solar irrigation has minimal regional impact, though risks arise if water use and dry-season area increase significantly. These results provide empirical evidence of changes in farmers’ water use after the transition to solar irrigation, but they are highly context-specific. Further research and tailored policies—such as water-saving practices, volumetric pricing, targeted scaling and smart subsidies—will ensure sustainable solar irrigation upscaling.